Step aside, Freud - There is a new co-analyst in town, and it is powered by artificial intelligence - Nitin P. Dharwadkar (Wolters Kluwer -Medknow Publications, 2023)
This article aimed to provide a mini-review of the current applications of artificial intelligence (AI) in the field of psychiatry, with a focus on its potential future uses and the associated benefits. PubMed and Google Scholar engines were searched using individual keyword followed by a search of more than one word in different permutations and combinations. The integration of AI technologies into psychiatric practices has introduced a new realm of possibilities, transforming the discipline and offering opportunities to enhance diagnostics, improve treatment outcomes, and reshape the landscape of mental health care. However, it is essential to recognize and address the potential negative consequences that may arise from the use of AI in psychiatry, including ethical concerns, privacy issues, and potential biases. By acknowledging both the opportunities and challenges, this article aimed to promote a balanced approach in harnessing the full potential of AI while mitigating any adverse impacts.